Effects of Changes in Nitrogen Availability on Nitrogen Gas Emissions in a Tropical Forest During a Drought. Issue 9 (11th September 2019) - Almaraz, Maya; Groffman, Peter M.; Porder, Stephen
Abstract: Atmospheric nitrogen (N) deposition in tropical forests may increase substantially in coming decades, stimulating a concomitant increase of soil N gas emissions. At the same time, climate change may increase the prevalence of drought, altering the processes that produce these gases (dominantly aerobic nitrification and anaerobic denitrification). This alteration is of particular concern if global changes increase the fraction of N gas released as nitrous oxide (N2 O; a greenhouse gas) relative to dinitrogen (N2 ). To simulate the effects of atmospheric N deposition on the amount and species of soil N gas emissions, we installed fertilized ion exchange resin bags across a hillslope in the Luquillo Experimental Forest of Puerto Rico. Our experiment took place during a severe drought, providing opportunities to consider how N addition and dry soil conditions interact. After 2 months of fertilization, we measured denitrification potential using a denitrification enzyme assay, which utilizes anoxic incubations where N and carbon limitation are relieved and nitrification is inhibited. We also measured N2 and N2 O emissions using a Nitrogen Free Air Recirculation Method (NFARM), which quantifies emissions from both nitrification and denitrification. Data from these two methods suggest that N inputs stimulated N2 O emissions associated with aerobic nitrification. Our data suggest that soil drying during the drought decreased N2 emissions associated with anaerobic denitrification and changed the spatial patterns of emissions in the landscape. Together these results suggest that, at least during a drought, N inputs increase N2 O emissions associated with nitrification, which may represent a positive feedback to climate change. Key Points: Nitrogen addition to tropical forest soils during a drought increased nitrogen gas fluxes by 450% Data from two different methods suggest that nitrogen inputs stimulated nitrous oxide emissions associated with aerobic nitrification Valleys were hot spots of nitrogen gas emissions in the landscape, and the only locations with substantial production of dinitrogen